Pengaruh Live Streaming,Customer Review Dan Gratis Ongkir Terhadap Keputusan Pembelian Tiktok Shop ( Studi Pada Pengguna Tiktok Shop Di Kabupaten Malang) - Saputri, Ika; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to test and analyze whether Live Streaming, Customer Review, and Free Shipping simultaneously influence the Purchase Decision of Tiktok Shop The type of research used in this study is a questionnaire with a quantitative approach. The population in this study is TikTok shop users in Malang Regency whose number is unknown. “This calculation shows that the sample size needed is 14x 5 = 70 respondents This study uses multiple linear regression analysis using the SPSS 25 application The results of this study indicate that there is a simultaneous influencer between the variables Live streaming (X1), Customer Review (X2) and Free Shipping (X3) on the purchase decision of TikTok Shop (Study on TikTok Shop Users in Malang Regency) Partially the variables Live Streaming Customer Review have a significant effect on the purchase decision of TikTok Shop while Free Shipping does not have a significant effect on the purchase decision of TikTok Shop  Keywords: Live Streaming, Customer Review, Free Shipping and Purchase Decision